2018
DOI: 10.1161/circep.117.005598
|View full text |Cite
|
Sign up to set email alerts
|

Does High-Intensity Endurance Training Increase the Risk of Atrial Fibrillation?

Abstract: URL: https://www.clinicaltrials.gov. Unique Identifier: NCT02039154.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
(59 reference statements)
0
21
0
8
Order By: Relevance
“…It is worth noting that exercise might not be recommended for individuals with mutations that cause atrial fibrillation and cardiomyopathy. Furthermore, intense endurance exercise appears to increase LA size in elite or recreational athletes and may subsequently predispose to AF (Iskandar et al, 2015; Elliott et al, 2018; Opondo et al, 2018). This is a dose-responsive effect that increases with lifetime hours of participation in endurance athletic activity (Flannery et al, 2017).…”
Section: Weight Loss and Exercise In Af Risk Reductionmentioning
confidence: 99%
“…It is worth noting that exercise might not be recommended for individuals with mutations that cause atrial fibrillation and cardiomyopathy. Furthermore, intense endurance exercise appears to increase LA size in elite or recreational athletes and may subsequently predispose to AF (Iskandar et al, 2015; Elliott et al, 2018; Opondo et al, 2018). This is a dose-responsive effect that increases with lifetime hours of participation in endurance athletic activity (Flannery et al, 2017).…”
Section: Weight Loss and Exercise In Af Risk Reductionmentioning
confidence: 99%
“…A revisão da literatura resultou em 22 artigos, os quais foram classificados de acordo com o tipo de publicação: 8 coortes, 9,10,11,12,13,14,15,16 5 Ensaios clínicos, 17,18,19,20,29 3 Estudos caso-controle 21,22,23 e 6 Estudos observacionais. 24,25,26,27,28,30 .…”
Section: Resultsunclassified
“…Ainda que um estudo apontou indivíduos com FA onde, na presença de exercícios físicos, a qualidade de vida deles aumentou, 18 em 12 estudos realizados com atletas profissionais ou de alto desempenho mostraram que esse tipo de exercício traz consequências arritmogênicas, favorecendo a FA, ou a remodelação atrial esquerda ou direita. 11,13,14,15,17,19,22,23,24,25,27,30 Além disso, o estudo de Reinhardt et al, detalha ainda, que, em atletas, ocorre com maior prevalência uma repolarização atrial do tipo precoce, aliados a uma frequência cardíaca (FC) menor. 12 Considerando essa análise da diminuição da frequência, Grundvold I, foi capaz de relacioná-la ao desenvolvimento de FA ao observar que homens saudáveis de meia idade, quando possuem uma FC menor que 100 bpm, têm um risco maior para surgimento de FA.…”
Section: Resultsunclassified
“… 33 The importance of substantial lifetime exposure to high-intensity endurance exercise has also been illustrated in a 2018 paper by Opondo et al reporting that 10 months of dedicated high-intensity exercise training induces changes in left atrial structure and mechanical function but without electrical consequences in middle-aged adults. 34 …”
Section: Introductionmentioning
confidence: 99%
“…33 The importance of substantial lifetime exposure to high-intensity endurance exercise has also been illustrated in a 2018 paper by Opondo et al reporting that 10 months of dedicated high-intensity exercise training induces changes in left atrial structure and mechanical function but without electrical consequences in middleaged adults. 34 Another potential exercise-related cardiac detriment is myocardial fibrosis (MF). A body of research has reported a heterogeneous profile of myocardial scarring in endurance athletes concerning prevalence, location, extent, aetiology and clinical significance.…”
Section: Introductionmentioning
confidence: 99%